Genome beginnings: rooting the tree of life - Lake, James A. (The Royal Society, 2009)
A rooted tree of life provides a framework to answer central questions about the evolution of life. Here we review progress on rooting the tree of life and introduce a new root of life obtained through the analysis of indels, insertions and deletions, found within paralogous gene sets. Through the analysis of indels in eight paralogous gene sets, the root is localized to the branch between the clade consisting of the Actinobacteria and the double-membrane (Gram-negative) prokaryotes and one consisting of the archaebacteria and the firmicutes. This root provides a new perspective on the habitats of early life, including the evolution of methanogenesis, membranes and hyperthermophily, and the speciation of major prokaryotic taxa. Our analyses exclude methanogenesis as a primitive metabolism, in contrast to previous findings. They parsimoniously imply that the ether archaebacterial lipids are not primitive and that the cenancestral prokaryotic population consisted of organisms enclosed by a single, ester-linked lipid membrane, covered by a peptidoglycan layer. These results explain the similarities previously noted by others between the lipid synthesis pathways in eubacteria and archaebacteria. The new root also implies that the last common ancestor was not hyperthermophilic, although moderate thermophily cannot be excluded.